Pemikiran Hukum Islam Tentang Fiqh Al-Awlawiyyat - Muhammad Hatta Diponegoro (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2018)
Basically, Islamic legal thought is very demanding a person's understanding of the Qur'an and alhadith, in the hope of formation of the application in line with the rules of Shari'a. Therefore, an in-depth understanding of an Islamic legal thought is necessary. Among the understanding is what is called the fiqh alawlawiyyat. Fiqh priority or fiqh in the priority scale balance is intended is a complex understanding of the study of Islamic law in a more proportional, with the intent and purpose for a mukallaf able to provide value for a practice in accordance with the views of Islamic Shari'a,because the majority of Muslims are considered not able to put the values ​​of worship and practice in accordance with the guidance of the Shari'a, then there is confusion that is happening to the Muslims. Confusion in determining this priority scale will be very dangerous if it continues to be left, then efforts to stem danger and clarify the problem need to be realized.Islamic Shari'ah has placed certain values ​​and stages for each act in accordance with its influence in the soul and life.as Islam also sets a certain level for things that are prohibited in accordance with its harm and badness for humans.The tendency to put forward something that is sunnah from the obligatory or overriding the more important of something important, it would discredit the value and purpose of the Shari'a.